2006
DOI: 10.1016/j.rmed.2005.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and high-resolution CT findings of pulmonary cryptococcosis in non-AIDS patients

Abstract: The objective of this study was to clarify clinical and high-resolution computed tomography (HRCT) characteristics in non-AIDS patients with pulmonary cryptococcosis. We analyzed the medical records and HRCT scans in 22 patients with pulmonary cryptococcosis from 1988 to 2003. Thirteen patients (59%) were immunocompetent and nine (41%) were immunosuppressed, seven of whom had diabetes mellitus. No patients exhibited extrapulmonary involvement. Nineteen patients (86%) were asymptomatic. Radiography revealed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
60
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 16 publications
(32 reference statements)
11
60
1
Order By: Relevance
“…The majority of patients in the current study presented with respiratory symptoms, including coughing (33.33%), expectoration (22.22%), fever (18.52%) and chest pain (14.81%), while only 3 patients (11.11%) were asymptomatic. In contrast to the present study, Kishi et al (10) reported that approximately one-third of immunocompetent patients with pul monary cryptococcosis were asymptomatic. Depending on the host immune status, cryptococcosis may disseminate from the lungs to other organs, including the CNS and brain.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The majority of patients in the current study presented with respiratory symptoms, including coughing (33.33%), expectoration (22.22%), fever (18.52%) and chest pain (14.81%), while only 3 patients (11.11%) were asymptomatic. In contrast to the present study, Kishi et al (10) reported that approximately one-third of immunocompetent patients with pul monary cryptococcosis were asymptomatic. Depending on the host immune status, cryptococcosis may disseminate from the lungs to other organs, including the CNS and brain.…”
Section: Discussioncontrasting
confidence: 99%
“…These aforementioned findings were similar to those of previous studies (23,28,29). Pulmonary cavitation has been more rarely reported in immunocompetent patients compared with immunocompromised patients (10). It has also been reported that cavitation demonstrates a long-term localized pulmonary abnormality, indicating that patients with cavitary pulmonary lesions may experience a more severe cryptococcal infection that requires a more aggressive antifungal therapy (31).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In one study using high-resolution CT, pulmonary nodules 10 mm with ground-glass opacity were considered to have a high possibility of malignancy and to be candidates for lung resection. 18 VATS is the recommended diagnostic and therapeutic approach in the management of SPNs due to cryptoccocosis 14 and small SPNs to rule out malignancy if a definite diagnosis by noninvasive imaging cannot be made. 18 Needle localization 19 and radiolabeled technetium localization 20 of small tumors with CT are reliable for identifying tumors for biopsy or wedge resection during thoracoscopy and may prevent the need for open thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…At least one study demonstrated a significantly higher frequency of cavitation by lung computed tomography among immunocompromised patients with cryptococcal lung infection (62.5%) than among immunocompetent patients (15.4%), but none of the immunocompromised patients in that study had human immunodeficiency virus infection (52). On the whole, cavitation appears to be more common among persons with mild to moderate immune compromise, such as that caused by diabetes, cirrhosis, or corticosteroid therapy, than among immunocompetent hosts (2,187,192). However, persons with severe immune compromise due to human immunodeficiency virus infection rarely have cavitary pulmonary cryptococcal infection; interstitial infiltrates and hilar lymphadenopathy are more common in this patient population (249,384).…”
Section: Histoplasmosis the Dimorphic Fungusmentioning
confidence: 98%